An Identification On The Role Of Behavioral Finance In Invesment (A Case Study At Pandawa Cooperative) - Imron, Febrini Khairunnisa; Kornitasari, Yenny; Hasyim, Wahid (BISNIS, 2020)
This study discusses the role of finance in investment decision making in the Pandawa Cooperative Case Study. Offering an irrational profit of 10% per month, the illegal investment case claimed 549 thousand victims with a total loss of Rp3.8 trillion. This research method uses a qualitative study with phenomenology to learn the truth about the role of finance in decision making which will be carried out through observations and discussions related to social phenomena related to financial roles in making investment decisions (case studies of the Pandawa Cooperative) directly in the Pandawa Cooperative case. After conducting the research process, it was concluded that the investment of the Pandawa Cooperative in investment decision making by three financial policies, namely overevidence, representative bias, and herding, which provided a role in making the Pandawa Cooperative investment decision.